Does Central Europe Import the Missing Women Phenomenon? - Alexander Stimpfle; David Stadelmann (Center for Research in Economics, Management and the Arts (CREMA), 2016)
We examine whether immigrants have brought the missing women phenomenon to Germany and Switzerland. Using a range of micro data since 1990, we find no systematic gender selection of foreigners collectively, but a group of Balkan, Chinese and Indian immigrants display comparatively high sex ratios at birth. Employing different estimation methods we consistently calculate around 1,500 missing girls in Germany (2003-2014) and Switzerland (1990-2014) combined from these selected Balkan and Asian immigrant groups. A Germany-specific measure of cultural adaptation has no substantial effect on the level of son preference, and Swiss-specific data indicate a skewed ratio for fourth parity births. With household survey data we attempt to identify underlying reasons for son preference in Germany, but find no robust associations for any socio-economic variable employed. However, the sex of older siblings tends to matter, and again Balkan, Chinese and Indian immigrants increase the boy-birth likelihood whereas immigrants collectively do not.
Keywords: J11; J16; 330; Missing Women; Sex Ratio at Birth; Son Preference; Migration